ANALISIS KECEPATAN PROSES DOWNLOAD PADA SINYAL HIGH SPEED DOWNLINK PACKET ACCESS (HSDPA) - Ari Pardani; Fitri Imansyah; F. Trias Pontia W (Faculty of Engineering, Universitas Tanjungpura, 2021)
In the use of a product, sometimes people do not really care whether the products are used in accordance with the advertising promotion of such products, one of which is advertising internet connection service. Internet service providers offer many advantages its products among which good data download speeds. This study describes the download speed of the signal HSDPA (High Speed Downlink Packet Access) using Sim card (card 3) where the research itself was carried out to test the speed of file downloads from the Adobe Flash Player version 22.0.0.209 is by downloading data at the same place and with the same file size.Data taken in this study is the duration of the download process from start to finish downloading. Furthermore, do some tests to determine the download speed of at 00:00 pm, 08:00 pm, 11:00 pm, 13:00 pm. And also determine where the most rapid hours to download the file, to determine how fast the download speeds are obtained in pontianak more precisely on Jalan Imam Bonjol Gg. Bansir 1. After a test known that the fastest clock is at 00:00 pm and 08:00 pm which has good speed.